The impact of different training intensities on athletes' immune system function and the management of upper respiratory traction infections: a narrative review - Rad, R. S. (Sport Sciences for Health, 2024)
Athletes employ high-intensity training to promote their physical fitness. However, high-intensity training can harm the immune system, making athletes susceptible to URTI, and negatively affecting their performance in sports. In addition, the athlete`s diet should be paid more attention to as it is another issue influencing the immune system, especially during the URTI. The present study attempts to discuss the impact of different training intensities on athletes' immune system function, as well as the management of upper respiratory traction infections. An online search was done in web of science (WoS), Ovid, Scopus, and PubMed (MeSH) databases with the following combination of keywords: "Upper Respiratory Tract Infections", "Exercise Training", and "Athletes". The results of our overview showed that regular and moderate-intensity training can reduce the relative risk of URTI, improve immune function and physical fitness. Moreover, we found that prolonged and high-intensity training can increase the relative risk of URTI, which leads to a decrease in aerobic performance, and also lessens physical fitness. Although high-intensity training can suppress the immune system, elite athletes should not stop training during the time of URTI. Based on the available evidence, it may be recommended to exercise during the URTI outbreak. Therefore, the first step in managing athletes` URTI is to reduce exercise intensity (the open window hypothesis may actually increase the susceptibility to URTI), with the utilization of nutritional strategies as the second step. However, athletes with severe and major URTI symptoms (e.g., severe sore throat, fever, cough, myalgia, shortness of breath, general fatigue) should avoid training and must have active rest (i.e., low-intensity exercise), as well as protein supplementation and low-intensity resistance training. Third, athletes with mild and minor URTI symptoms (e.g., runny nose, sinus congestion, mild sore throat) can perform aerobic training and moderate-intensity training, and benefit from improved immune function according to the J-shaped model. Functional nutritional strategies include avoiding sudden dietary changes, receiving 50% of total daily calories from carbohydrates consumption: 30-90 g/h in competitions (depending on the intensity and duration of exercise), protein consumption: 1.3 to 1.8 g/kg bw/day, flavonoids intake, herbal supplements intake, probiotic supplementation intake, and taking vitamins C and D.